Physical activity variability with the risk of type 2 diabetes: findings from a National Prospective Cohort Study - Zehua Wang; Aiping Zhao; Chenxing Ma; Zhen Zhang; Yazhong Zhang (Endokrynologia Polska)
INTRODUCTION: The objective was to investigate the association between physical activity variability (PAVar) and the risk of type 2 diabetes mellitus (T2DM) among middle-aged and older adults. MATERIAL AND METHODS: This longitudinal cohort study utilized data from the China Health and Retirement Longitudinal Study (CHARLS), following participants from 2011 to 2020. A total of 3970 individuals with sufficient physical activity (PA) data were categorized into quartiles based on the coefficient of variation (CV) for PAVar. The incidence of T2DM was assessed using Cox proportional hazards models adjusted for demographic, socioeconomic, and lifestyle factors. Mediation analysis was performed to evaluate whether sleep duration influenced the relationship between PAVar and T2DM risk. Sensitivity analyses excluded individuals with missing baseline data to ensure the reliability of the findings. RESULTS: Higher PAVar was associated with an elevated risk of T2DM. In fully adjusted models, participants in the highest CV quartile had a 70% greater risk of developing T2DM [hazard ratio (HR): 1.70, 95% confidence interval (CI): 1.54–1.88] compared to those in the lowest quartile. Mediation analysis showed that sleep duration accounted for 18.5% of the total effect of PAVar on T2DM risk. Sensitivity analyses confirmed the robustness of these findings. CONCLUSIONS: This study demonstrates the harmful effects of high PAVar on T2DM risk and underscores the need to promote consistent physical activity patterns and adequate sleep to prevent diabetes, particularly in aging populations.